Are the mental representations of people with osteoarthritis consistent with the International Classification of Functioning Disability and Health?. (August 2013) - Pollard, Beth; Dixon, Diane; Johnston, Marie
Abstract : Purpose : This study examined whether the mental representations of people with osteoarthritis (OA) were consistent with the International Classification of Functioning Disability and Health (ICF) model. Methods : A geographical cohort of 202 people with OA about to have joint replacement surgery completed postal questionnaires. Mental representations were measured by asking participants what they were hoping for from their joint replacement. Two expert judges classified these illness representations to the main ICF constructs of Impairment (I), Activity Limitation (A) and Participation Restriction (P). Results : There was strong agreement between the expert judges. There were a similar number of illness representations for each of the ICF constructs. The primary biomedical route of the ICF model was suggested by the ordering of the participants' illness representations i.e. I to A to P. Conclusions : The mental representations of people with OA were consistent with the ICF theoretical framework with all three ICF constructs of importance. It appeared that people with OA implicitly apply a biomedical causal model of disability, suggesting that treatments and interventions aimed at reducing impairment may only affect P indirectly, through A. Additionally, the methods provide a novel way of exploring the potential causal relationships between constructs of the ICF model.